(untitled) (Research, Society and Development, 2022)
Brazil has 28 million elderly people, and this number is expected to double in the coming decades, which may favor the onset of mental illnesses, such as depression. This pathology can have consequences that directly interfere with health conditions, influencing quality of life in a negative way, especially in physical and psychosocial functions. Objective: to identify the prevalence of depression in non-institutionalized elderly people who participate in activities at the Service Center for Coexistence and Strengthening of Bonds for the Elderly in the city of Imperatriz-MA. Methodology: This is an exploratory field research with a quantitative approach carried out in August 2021 in a community service center for non-institutionalized elderly in the city of Imperatriz - MA. Data were obtained through interviews based on sociodemographic and socioeconomic conditions, physical activities, Mini Mental State Examination and the Geriatric Depression Scale. Results: Predominance of women (75,7%), aged between 70 -79 years (50%), widowed, (37.1%), low schooling (67,1%), frequency of carrying out activities in the institution (1 to 3 times a week) (84.3%), preservation of cognition (58.6%) and suspected depression (95,1%). Conclusion: In view of this situation, the consequences of this comorbidity on the quality of life of the elderly are visible. Therefore, this work shows evidence of the need for attention and tracking for the non-institutionalized elderly, due to the prevalence and consequences exposed on depression.